CLUSTERING POTENSI PADI DI PROVINSI NUSA TENGGARA TIMUR MENGGUNAKAN STANDARD K-MEANS DAN TRAJECTORY K-MEANS - Jofri Ardo Tiganna Sembiring (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
The Agricultural sector is the mainstay of the economy of East Nusa Tenggara, contributing 28,87 percent to the regional GDP in 2024. Of this amount, the food crop sub-sector contributed 22,94 percent, demonstrating the strategic role of food commodities in the regional economic structure. Rice, as the main staple food of the community, has high economic and social value because it directly affects food security and the welfare of the population. This study aims to cluster districts/cities in NTT based on rice potential using Standard K-Means and Trajectory K-Means methods, utilizing indicators such as harvested area and production. The analysis results show that the optimal number of clusters is four. The evaluation shows that Standard K-Means produces better grouping quality, while Trajectory K-Means remains relevant for identifying patterns of change over time. These findings confirm that region grouping based on rice potential can be the basis for more effective, efficient, and sustainable policy-making in strengthening the food sector in NTT.